Measuring Production Capacity Utilization and Its Impact on Manufacturing Performance and Environment - Shahidul, M. I.; M. S., Osman; S. T., Syed Shazali; A., Yassin; C. H., Tinga; A. H., Hishamuddin; S. M, Azrin; M. A. F. K., Adzlan (ENCON 2013, 2013)
Underutilized of machinery capacity appears as non-value added hidden factor in production process which contributes to reduce production performance. In that context, this research aims to estimate Capacity Utilization (CU) of production machinery by using short run production function for evaluating its impact on production efficiency and environment quality. Short run production function is developed based on engineering concept of capacity measurement. Developed model has tested in a manufacturing industry which reveals machinery was operated with 70% CU and 73% efficiency. Additionally, degree of CU appears positively associated with production efficiency and negatively associated with industrial wastage. Despite a few limitations, CU model appears a useful tool for optimizing production performance and environment quality. However, this study concludes that underutilize CU contributes to increases industrial wastage which negatively associates with environment quality. Further study is essential for measuring effect of machinery breakdown and working environment on capacity utilization.